If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = 3y + 13 Reorder the terms: 2x = 13 + 3y Solving 2x = 13 + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '2'. x = 6.5 + 1.5y Simplifying x = 6.5 + 1.5y
| X=5x+y | | u=n^2+9n-20 | | 1/4(x-3)=5 | | un=n^2+9n-20 | | 2a+12=-60 | | 19z+(-13z)+(-14z)=88 | | 7z*7z= | | 7x+10=x+120 | | 10-2(m+5)=16 | | 42g-45g+(-93)=-12 | | z*z= | | 13-6x=-38 | | 91v-16v-61v-12v-v=95 | | 16y-24=4y | | 16z-48=4z | | 51=3*3+2*3*h | | X^2+9x-3=5x-7 | | 3x-(x+1)=6m+1 | | 2m+7+3m=-33 | | 6.25y=9 | | 73-x=2x+3 | | 3000=300(10+x) | | [x-2]=-4 | | 2a-38a+43a+(-29a)=66 | | 1.26=2z-8 | | 3000=300x+3000 | | -5.75y=9 | | 3(95-6x)=1x-152 | | 2x+(1-3x)=-7 | | e^3x-1=(e^6)-x | | (0.5x-3)(0.6x+3)=0 | | 27k+(-24k)=24 |